Ultrasound, anthropometry and bioimpedance: a comparison in predicting fat deposition in non-alcoholic fatty liver disease - Vitturi, Nicola; Soattin, Marta; De Stefano, Fabio; Vianello, Daniela; Zambon, Alberto; Plebani, Mario; Busetto, Luca (Eating and weight disorders, 2015)
Purpose The aim of our study was the evaluation of anthropometric measurements [waist circumference and sagittal abdominal diameter (SAD)] and abdominal bioelectrical impedance analysis ( BIA) (ViScan, TANITA) in comparison to several abdominal ultrasonographic (US) measurements to estimate visceral fat deposition and liver steatosis in a population of 105 subjects. Methods All 105 patients underwent a complete anthropometric evaluation, blood sample for the determination of total cholesterol, HDL cholesterol, triglycerides, glucose, insulin, high-sensitivity C-reactive protein, BIA and US measurements (peritoneal, pre-peritoneal, peri-renal, para-renal and peri-hepatic fat thickness). Results All the ultrasonographic markers considered in our study are related to the presence of non-alcoholic fatty liver disease (NAFLD), and so is true for SAD. Comparing ROC curves, peritoneal fat tissue thickness, SAD and ViScan visceral index are significantly better than waist circumference in predicting the presence of NAFLD (AUC 0.79 ± 0.04; 0.81 ± 0.05; 0.82 ± 0.04 vs 0.76 ± 0.05, respectively). Conclusions According to our data, various methods may be useful in evaluating NAFLD, but only ViScan visceral index, US peritoneal fat thickness and SAD are better than waist circumference. Among them, SAD is the most promising, due to its small cost and time consumption.